Longitudinal study of the effect of sporidesmin toxicity on lamb production and serum biochemistry in a flock of 46 Romney ewes using a standardised measure of liver damage. - Lawrence KE; Flay KJ; Munday JS; Aberdein D; Thomson NA; Vignes M; Ridler AL (Massey University, 2022)
AIMS: To evaluate the effect of sporidesmin toxicity on production outcomes and serum biochemistry analytes in mixed age Romney ewes, using a standardised measure of liver damage. METHODS: This was a prospective longitudinal study following 46 mixed age Romney ewes from sporidesmin intoxication in April 2019, to slaughter 8 months later. The ewes were blood-sampled up to eight times, with a panel of serum biochemistry tests performed on the final six samples. However, only gamma-glutamyl transferase (GGT) activity was measured in the first two samples collected at the end of sporidesmin intoxication and 2 weeks later. Body condition score, ewe weight and production data were also recorded. Using a standardised liver score, based on histology of liver samples collected at slaughter, ewes were assigned to one of three liver disease categories (LDC); low, middle, and high. These were then used as the outcome or predictor variables for statistical analyses. Finally, two separate decision tree models, using recursive partitioning (RP), were fitted to the biochemistry data and to the GGT data collected at FE outbreak, to predict ewes in the low LDC. RESULTS: There was no evidence of a difference for the effect of LDC on ewe weight (p = 0.86) with ewes, on average, gaining weight to weaning. Weaning percent, lamb rearing percent and ewe flock efficiency were lower in ewes with high LDC, and scanning-to-weaning lamb loss was significantly higher in sheep with high LDC (p = 0.02). Serum activities of GGT and glutamate dehydrogenase and concentration of globulin were significantly lower in sheep with low LDC than in sheep with middle or high LDC (p < 0.05). However, there was no evidence of a difference for the effect of LDC on other biochemistry variables (p > 0.05). The final RP model for the biochemistry data categorised ewes as low LDC if their GGT was <122 IU/L, 3 months after sporidesmin intoxication, or if their GGT was <514 IU/L, <18 days after sporidesmin intoxication. CONCLUSIONS AND CLINICAL RELEVANCE: Sheep with gross and histological evidence of severe sporidesmin-induced liver damage were able to maintain or gain body weight, suggesting that sporidesmin intoxication alone is not causative of poor body condition. Similarly, many of the serum biochemistry tests were not associated with evidence of liver damage. Lamb production was reduced in ewes with evidence of severe liver damage and the decision tree model showed promise as a basis to select ewes for culling.
CAUL Read and Publish Agreement.
Keywords: Sheep; New Zealand; Facial Eczema; Sporidesmin; Liver damage; Gamma-glutamyl transferase; 0707 Veterinary Sciences